Analysis of Factors Affecting Purchasing Interest on TikTok Shop - Valen Tjahyadi (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
As the phenomenon of technology and online shopping trends continues to grow, TikTok Shop has emerged as one of the most popular social media-based e-commerce platforms, especially among the younger generation. This study examines several factors, including Price, Promotion, Influencer Marketing, Service Quality, and Cashback/Discount. Employing a quantitative methodology, the study surveyed 100 participants. The data were analyzed using SPSS to assess the impact of each independent variable on Purchase Intention. The findings reveal that Price, Influencer Marketing, and Service Quality significantly influence Purchase Intention, whereas Promotion and Cashback/Discount exhibit a lesser impact. These results offer valuable insights for business stakeholders in crafting effective marketing strategies on the TikTok Shop platform